Elevated serum α-fetoprotein levels in patients with chronic hepatitis C virus genotype 4: not the end of the story. Issue 3 (March 2016) - Abdel-Razik, Ahmed; Mousa, Nasser; Abdel-Aziz, Mahmoud; Elhelaly, Rania; Elzehery, Rasha; Zalata, Khaled; Elkashef, Wagdi; Fouda, Ossama; Awad, Mahmoud; Hafez, Mohamed; Eldars, Waleed
Abstract : Background and aim: Elevated serum α-fetoprotein (AFP) is not uncommonly seen among patients with chronic hepatitis C. This study aimed to identify clinical characteristics, histological characteristics, and biochemical markers associated with increased serum AFP levels in hepatitis C virus genotype 4-infected patients with no evidence of hepatocellular carcinoma and to determine the effect of lifestyle modification on these parameters. Methods: The study included 447 chronic hepatitis C patients with no evidence of hepatocellular carcinoma and 100 healthy controls. They underwent liver biopsies, homeostasis model assessment-insulin resistance (HOMA-IR), measurement of serum insulin, leptin, adiponectin, tumor necrosis factor-α, and interleukin-6 levels by an enzyme-linked immunosorbent assay, and assessment of AFP levels. Eighty patients with HOMA-IR greater than 3 received prospective longitudinal lifestyle intervention. Results: In a multivariate analysis, platelet count less than 140×10 3 /cm, a mean platelet volume of at least 9.5 fl, a neutrophil–lymphocyte ratio (NLR) of at least 2, an aspartate transaminase level of at least 55 IU/l, a γ-glutamyl transpeptidase level of at least 40 IU/l, an albumin level of up to 3.8 g/dl, HOMA-IR greater than 3, a leptin level of at least 10 pg/ml, an iron level of at least 165 μg/dl, a ferritin level of at level 175 ng/ml, and hepatic fibrosis F3–F4 were found to be independently associated with elevated AFP levels. The lifestyle intervention significantly improved BMI, platelet indices, NLR, γ-glutamyl transpeptidase, leptin, leptin/adiponectin ratio, tumor necrosis factor-α, interleukin-6, HOMA-IR, and AFP levels. Conclusion: Elevated insulin resistance, leptin, serum iron, ferritin, mean platelet volume, NLR, and advanced fibrosis, as well as decreased platelet count and serum albumin, are independently associated with an elevated AFP level. Lifestyle modification can improve (reduce) insulin resistance, leptin, leptin/adiponectin ratio, platelet count and their indices, NLR, and AFP level.